Efficiently targeted therapy of glioblastoma xenograft via multifunctional biomimetic nanodrugs - Zhipeng Yao; Xiaochun Jiang; Hong Yao; Yafeng Wu; Fan Zhang; Cheng Wang; Chenxue Qi; Chenhui Zhao; Zeyu Wu; Min Qi; Jia Zhang; Xiaoxiang Cao; et al. (Biomaterials Research, 2022)
Abstract Background Glioblastoma multiforme (GBM) is a fatal malignant primary brain tumor in adults. The therapeutic efficacy of chemotherapeutic drugs is limited due to the blood-brain barrier (BBB), poor drug targeting, and short biological half-lives. Multifunctional biomimetic nanodrugs have great potential to overcome these limitations of chemotherapeutic drugs. Methods We synthesized and characterized a biomimetic nanodrug CMS/PEG-DOX-M. The CMS/PEG-DOX-M effectively and rapidly released DOX in U87 MG cells. Cell proliferation and apoptosis assays were examined by the MTT and TUNEL assays. The penetration of nanodrugs through the BBB and anti-tumor efficacy were investigated in the orthotopic glioblastoma xenograft models. Results We showed that CMS/PEG-DOX-M inhibited cell proliferation of U87 MG cells and effectively induced cell apoptosis of U87 MG cells. Intracranial antitumor experiments showed that free DOX hardly penetrated the BBB, but CMS/PEG-DOX-M effectively reached the orthotopic intracranial tumor through the BBB and significantly inhibited tumor growth. Immunofluorescence staining of orthotopic tumor tissue sections confirmed that nanodrugs promoted apoptosis of tumor cells. This study developed a multimodal nanodrug treatment system with the enhanced abilities of tumor-targeting, BBB penetration, and cancer-specific accumulation of chemotherapeutic drugs by combining chemotherapy and photothermal therapy. It can be used as a flexible and effective GBM treatment system and it may also be used for the treatment of other central nervous systems (CNS) tumors and extracranial tumors.